Pendaftaran Peralihan Tanah Milik Kaum yang Sudah Terdaftar atas Nama Mamak Kepala Waris di Kota Padang - Yahya, Ilham; Warman, Kurnia; Andora, Hengki (Universitas Ekasakti, 2023)
Land title certificates are strong evidence as confirmed in Article 19 paragraph (2) letter c UUPA and Article 32 paragraph (1) Government Regulation Number 24 of 1997 concerning Land Registration. The problem formulation in this research is: How is family land registered in the name of the head of the heir in Padang City? Why do disputes arise in recording the transfer of land rights belonging to registered people to third parties in Padang City, and how are these disputes resolved? The research method used is qualitative research and empirical juridical research. The results of the research are the Registration of clan-owned land in the name of the chief heir in Padang City. Land originating from clan customary rights can be transferred in the name of clan members based on the Approval/Statement of Clan Approval that has been given by the Agency Agency. Land. The process of transferring rights to customary community land in the name of the chief heir is by submitting an application to the Head of the Land Office so that the community's customary land is registered in the name of the clan or Chief. The Heirs use a Statement of Physical Control of the Land Plot signed by the Head of the Heirs.